Alterman’s Research Review - Mihajlovna, Zorina Violetta (International Journal of Psychosocial Rehabilitation, 2020)
In this article, we have analyzed the research of Natalie Alterman, which offers to classify high school teachers not only as motivating or demotivating but to review the teachers’ motivating styles more multifacetedly. The concept of the theory of self-determination was applied in this study; a more detailed analysis of the motivation’s style is proposed to achieve further progress in this field of research and practice. As a result of the study, we have concluded that a consistent approach to the motivation and demotivation of learning is justified.